Housing affordability in the state of Melaka - Mohamed Osman, Mariana; Rabe, Noor Suzilawati; Abdullah, Muhammad Faris; Rosli, Nur Farhanah; Zainudin, Farah Eleena (Malaysian Institute of Planners, 2017)
Housing is a basic need to man. It provides shelter and comfort from the elements and improve quality of life of the residents. Hence, housing should be affordable to all. This paper assesses the housing affordability for the districts in Melaka. This was achieved by calculating the median multiple of the price income ratio and comparing the score to the housing affordability index. Secondary data were obtained from reports published by the governmental agencies. The results show that housing is mostly moderately unaffordable in the districts of Melaka. Additionally, housing affordability has improved from 2012 to 2014 in majority of the districts.